Efektivitas Pembelajaran Makhârij Al-Hurf Secara Virtual (Studi Kasus Terhadap Komunitas Whatsapp Tahfizh) - Rizky Aulia Isyatami Hidayat (Cendekia, 2021)
The development of technology affects various sectors, one of which is the education sector. Based on these technology advances, there is a Whatsapp Tahfizh (WAFI) community that accommodates anyone who want to learn the Qur'an but has limited time because of busyness. The learning system in WAFI is virtual based, so it can be followed by a wide range of people both ages and professions. One of the tahsin classes provided by WAFI is makhârij al-hurf class. Using the concept of virtual learning, this is certainly an option for those who want to learn the Qur'an but have a little time. Because during the learning process each participant can deposit at any time the reading on the condition that they meet the target on that day. Especially with the covid 19 pandemic, the learning of the Qur'an in WAFI provides a good news in the treasures of learning the Qur'an. The purpose of this study is to measure the effectiveness of learning makhârij al-hurf virtual hammering hosted by WAFI. The research method used is qualitative with a case study approach. Respondents taken were correctors as well as management in the WAFI community, active participants in the class makhârij al-hurf also based on data and experiences collected by the author who is one of the correctors in the class makhârij al-hurf. The results of the study conducted that learning makhârij al-hurf virtually have a positive impact although not as much as face to face learning (directly). However, WAFI remains a solution for anyone who wants to learn the Qur'an and has limited time due to busyness.